Cumulative Disadvantage and the Role of Transportation in Community Supervision. (July 2018) - Bohmert, Miriam Northcutt; DeMaris, Alfred
Drawing from cumulative disadvantage theory, we are the first to examine the role of transportation disadvantage among other known challenges for women on community supervision. We create a composite measure of transportation disadvantage using factor analyses and data for 362 women on probation and parole in one Midwestern state: It is used to predict arrest and conviction using multiepisode event history analysis and conditional logistic regression. Consistent with cumulative disadvantage theory, the results suggest each additional disadvantage makes women more vulnerable, over and above the other disadvantages. Transportation disadvantage is a significant and entrenched feature in criminal justice-involved women's lives. The import of modeling all available recidivism events, given the entrenched nature of criminal justice system involvement, cannot be overstated.